A inserção do Brasil na política internacional de direitos humanos da pessoa idosa - Notari, Maria Helena de Aguiar; Fragoso, Maria Helena J. M. de Macedo [UNESP] (Fundação Getúlio Vargas (FGV), Escola de Direito, 2011)
Este artigo propõe-se a estudar a evolução da proteção internacional dos direitos humanos da pessoa idosa e a posição do Brasil nas discussões sub-regionais, regionais e multilaterais que ocorrem na atualidade, considerando O presente contexto mundial de envelhecimento da população e os novos desafios que essa realidade implica.

Due the effect of aging at the world population and the new challenges that this new reality implies, this article has the objective to study the evolution of the international Protection of Ageing People Human Rights and also the Brazilian government position at the contemporary subregionals, regional and multilateral discussions.
Brazilian insertion in the international politics of ageing people human rights
Keywords: Direitos humanos; Convenção internacional; Pessoa idosa; Human Rights; International convention; ageing people